2021
DOI: 10.1177/08862605211020981
|View full text |Cite
|
Sign up to set email alerts
|

Health Correlates of Intimate Partner Violence and Help-seeking Among Unauthorized Immigrant Women

Abstract: Intimate partner violence (IPV) research on immigrant women who are unauthorized is particularly scarce, despite unique vulnerabilities associated with their documentation status that may impact help-seeking and health outcomes. The purpose of this study was to document the frequency of lifetime IPV and related help-seeking behaviors, and examine the relationship between IPV, major depressive disorder (MDD), post-traumatic stress disorder (PTSD), and health-related quality of life (HRQL) among a community heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Regarding IPV types, Chen et al (2009) found physical, sexual, and psychological IPV to be related to common mental health disorders and mental health disorder symptoms, respectively, among Hispanic women. Similarly, physical IPV was related to poorer mental health quality of life scores among undocumented Hispanic immigrant women (Shuman et al, 2014). However, Chen et al (2009) presented mixed findings on the association between IPV types and general mental health outcomes among Hispanic women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding IPV types, Chen et al (2009) found physical, sexual, and psychological IPV to be related to common mental health disorders and mental health disorder symptoms, respectively, among Hispanic women. Similarly, physical IPV was related to poorer mental health quality of life scores among undocumented Hispanic immigrant women (Shuman et al, 2014). However, Chen et al (2009) presented mixed findings on the association between IPV types and general mental health outcomes among Hispanic women.…”
Section: Resultsmentioning
confidence: 99%
“…Rodriguez et al (2010) showed that IPV-victimized Hispanic women were significantly more likely to experience depression, both currently and persistently over time, compared to their non-IPV-victimized Hispanic counterparts. Indeed, results showed that undocumented Hispanic immigrant women with versus without experiences of IPV at any point in their lifetime were more likely to have a diagnosis of major depressive disorder (Shuman et al, 2014). Notably, nonsignificant or negative findings were found for three of the reviewed studies in this area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this study pushes forward the moderating role of PA on SNS in the willingness of IPV victims to seek online help. Existing research suggests that most IPV victims are reluctant to seek outside assistance or social support [ 34 , 59 ]. However, when IPV victims have a high degree of PA in social networks, they realize that their privacy is fully protected, resulting in a strong willingness to seek help online.…”
Section: Discussionmentioning
confidence: 99%
“…Second, studies used a variety of instruments to capture IPV-V rates including versions of the Conflict Tactics Scale, the Abuse Assessment Screen (e.g., Ingram, 2007), and qualitative coding of asylum applications (e.g., Cuneo et al, 2021). Although some of the scales used to assess IPV-V were validated in English, many of the scales were translated into different languages, and construct validity was not assessed after translation (e.g., Shuman et al, 2021). Thus, it is possible that errors in translation or back-translation biased estimates.…”
Section: Ipv Victimization Among Immigrantsmentioning
confidence: 99%